Geodetic activities in Lithuania related to Aalborg University - Borre, Kai (Geodesy and Cartography, 2012)
Review paper in English – Geodetic activities in Lithuania related to Aalborg University by Kai Borre, Aalborg University. First published online: 03 Aug 2012